The Euro – A Tale of 20 Years: What Are the Priorities Going Forward? - Marco Buti; Maya Jollès; Matteo Salto (Intereconomics, 2019)
First, we need to recall the initial objectives set for the euro and how these have changed over time, notably due to the weaknesses that came to the fore throughout the recent crisis. This also calls into question the policy choices made during the crisis and the priorities going forward.
Keywords: 330